Global justice, socials rights and pluralism [Justicia global, derechos sociales y pluralismo] (2010)
In this article I face one of the actual challenges that is confronting the philosophical reflection: trying to accomplish a believable defense of the moral universalism. I propose a version that attempts to expose two of the greatest normative needs that are conditioning its plausibility and that according to the majority of thoughts it result incompatible. On the one hand, this is based on a conception of our basic rights sufficiently minimalistic that the outcome is consent with pluralism. On the other hand, it is sufficiently inclusive that allows the defense of the universal social rights. From which we justify the duty to redistribute the world's wealth, like a critical solution to relieve the pain and suffering of a number every time larger of people submitted to a life of extreme poverty.